Pengembangan Bahan Ajar Bahasa Indonesia pada Materi Puisi Berbasis Kearifan Lokal Kota Tanjung Balai pada Kelas V SD Negeri 137957 TA 2024/2025 - Yulanda Fathira Simamora; Eva Betty Simanjuntak; Apiek Gandamana; Edizal Hatmi; Dody F. Pandimun Ambarita (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
This study reveals how difficult it is to teach poetry appreciation to students. The research used in this study is research and development (R&D). The subjects in this development research were 30 fifth-grade students of SD Negeri 137957 Tanjungbalai in the 2024/2025 Academic Year. While the object of this research and development is the Indonesian Language module based on local wisdom of Tanjungbalai city on poetry material for fifth-grade elementary school. The data collection technique for this study used interviews, questionnaires, and tests. The analysis technique of this study tested the validity analysis module, and the effectiveness analysis of the module. Based on the results of the study, it was concluded that simple teaching materials based on local wisdom in Indonesian Language learning chapter 10 topic b "Creativity" material "Poetry" for fifth grade was delivered "very appropriate" with a percentage of 90.4%, thus it can be used as a supporting tool in teaching and learning activities in fifth grade of SD Negeri 137957 Tanjung Balai city. Regarding the effectiveness of the teaching materials, it can be concluded that the improvement in student learning outcomes before and after the use of simple teaching materials based on the local wisdom of the Tanjung Balai community was 73.34%, which was considered "very effective" for use. The results of the responses from educational practitioners obtained a score of 45 out of a maximum score of 48, with a percentage of 93.75%, categorized as "very practical." Based on the results of the student response questionnaire, a percentage of 92.12% was categorized as "very practical." This indicates that the teaching materials successfully attracted students' attention, facilitated their understanding of the material taught, and had a positive impact on the learning process in the classroom.